Integrated 3D survey of the first Franciscan observance settlement in Portugal: The convent of Santa Maria de Mosteiró in Valença (Alto Minho, North of Portugal) - Volzone, R.; Ferretti, R. (Architectures of the soul: Diachronic and multidisciplinary readings, 2022)
The continuous abandonment of convents in Portugal, culminating with the 1834 decree of dissolution of religious orders, led to the loss of their original function and values. This study analyzes the physical legacy – mostly altered, abandoned, or in a ruinous state – of the first Franciscan Observance settlements (1392) in the Portuguese territory at the Northern border with Spain, with focus on the convent of Santa Maria de Mosteiró (Valença, north of Portugal). This paper aims to understand the historical and current values of these sites through a knowledge-based approach by conducting historical research and surveys. The methodology combines traditional and innovative techniques: historical research with current analysis of the built structures through integrated digital survey techniques. These first results constitute a support tool for the conservation, protection, and enhancement of this cultural heritage. They also enable comparative analysis with the other case studies in Portugal, Spain, and Italy in order to understand the typological model at the basis of the Franciscan Observance in Southern Europe.